The changing landscape of vancomycin-resistant Enterococcus faecium in Australia: a population-level genomic study. (4th September 2018) - Lee, Robyn S; Gonçalves da Silva, Anders; Baines, Sarah L; Strachan, Janet; Ballard, Susan; Carter, Glen P; Kwong, Jason C; Schultz, Mark B; Bulach, Dieter M; Seemann, Torsten; Stinear, Timothy P; Howden, Benjamin P
Abstract: Background: Vancomycin-resistant Enterococcus faecium (VREfm) represent a major source of nosocomial infection worldwide. In Australia, there has been a recent concerning increase in bacteraemia associated with the vanA genotype, prompting investigation into the genomic epidemiology of VREfm. Methods: A population-level study of VREfm (10 November–9 December 2015) was conducted. A total of 321 VREfm isolates (from 286 patients) across Victoria State were collected and sequenced with Illumina NextSeq. SNPs were used to assess relatedness. STs and genes associated with resistance and virulence were identified. The vanA -harbouring plasmid from an isolate from each ST was assembled using long-read data. Illumina reads from remaining isolates were then mapped to these assemblies to identify their probable vanA -harbouring plasmid. Results: vanA -VREfm comprised 17.8% of isolates. ST203, ST80 and a pstS (−) clade, ST1421, predominated (30.5%, 30.5% and 37.2%, respectively). Most vanB- VREfm were ST796 (77.7%). vanA -VREfm were more closely related within hospitals versus between them [core SNPs 10 (IQR 1–357) versus 356 (179–416), respectively], suggesting discrete introductions of vanA -VREfm, with subsequent intra-hospital transmission. In contrast, vanB -VREfm had similar core SNP distributions within versus between hospitals, due to widespread dissemination of ST796. Different vanA -harbouring plasmids were found across STs. With the exception of ST78 and ST796, Tn 1546 transposons also varied. Phylogenetic analysis revealed Australian strains were often interspersed with those from other countries, suggesting ongoing cross-continental transmission. Conclusions: Emerging vanA -VREfm in Australia is polyclonal, indicating repeat introductions of vanA -VREfm into hospitals and subsequent dissemination. The close relationship to global strains reinforces the need for ongoing screening and control of VREfm in Australia and abroad.